Dental aesthetics and self-esteem in adolescents (2011)
Objective: The aim of this study was to investigate the relationship between dental aesthetics and self-esteem in adolescents. Methods: The sample was 387 randomly selected high school adolescents between 13 and 16 years of age. A clinical examination to evaluate dental aesthetics was conducted using the Dental Aesthetic Index (DAI). Self-esteem was assessed with the Rosenberg's Self-esteem Scale. The statistical analysis included a descriptive analysis and means comparison, which was made through t-Student and ANOVA tests. DAI was correlated to Rosenberg's Self-esteem Scale with Spearman's rank correlation coefficient. The data collected was analyzed by using the SPSS program version 17. Results: The mean DAI score was 34.2 (SD=14.2) and self-esteem was 22.6 (SD=4.6). The low socioeconomic status (SES) group had the highest levels of DAI and the lowest levels of self-esteem. A weak, but statistically significant, negative correlation was found between DAI scores and Rosenberg's self-esteem scale (r=-0.1, p<0.05). According to age, in adolescents aged sixteen there was a slight correlation with both variables (p>0.05). Regarding gender, in female individuals a negative weak correlation (r=-0.14, p<0.05) was observed. No statistically significant difference was shown among SES groups. Nevertheless, there was a positive slight correlation in the middle SES group (p>0.05). Conclusions: The outcomes generated by this investigation can improve our understanding of how the correlation between dental aesthetics and self-esteem may fluctuate because of the SES variability. © 2011 Universidad del Valle, Facultad de Salud.